Impingement-type bony morphology was related to cartilage defects, but not pain in professional ballet dancers` hips - Mayes, S.; Smith, P.; Cook, J. (Journal of Science and Medicine in Sport, 2018)
Objectives: Professional ballet dancers may have hip bony morphology that predisposes them to cartilage or labral injury. However, the relationship between bony morphology and pathology has not been investigated in ballet. This study investigates associations between bony morphology, chondrolabral defects and hip pain in ballet dancers. Design: Cross-sectional study. Methods: 33 male and female professional ballet dancers, (mean age 27 years (range 19-39)), completed questionnaires with hip pain measured on a visual analogue scale; and underwent 3.0-T magnetic resonance imaging (3T MRI) to measure lateral centre edge angles (LCEA), alpha angles in the anterior and superior position, femoral neck-shaft angles (NSA) and acetabular version angles; and to detect acetabular labral tear and articular cartilage defects. Results: Seventeen dancers (51.5%) had impingement-type (alpha angle > 50.5° or acetabular version <10° or >20°) and 19 (58%) had instability-type (LCEA < 25° or NSA > 135°) bony morphology. Cartilage defect prevalence was higher in dancers with impingement-type bony morphology (n = 14) compared to those without impingement-type morphology (n = 4, p = 0.001). There was no relationship between instability-type bony morphology and cartilage defects (p > 0.05). There was no relationship between labral tears and bony morphology (p > 0.05). Neither chondrolabral pathology nor any morphological feature were associated with hip pain (p > 0.05 for all). Conclusions: Impingement-type bony morphology was related to cartilage defects, but not labral tear. Hip pain was not associated with pathology or bony morphology. Longitudinal studies are warranted to determine if bony features, such as cam morphology, acetabular retroversion or anteversion, are precursors to symptomatic hip joint injury or osteoarthritis.